Recovering Environmental and Economic Traditions in the Islamic World - Al-Daghistani, Sami, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2025)
Recovering Environmental and Economic Traditions in the Islamic World is an interdisciplinary volume that interrogates varied approaches to environmental and economic thought in classical Islam and in a few contemporary case studies. The contributions in this volume critique the dominant economic system and its perspective on the environment as a commodity across the boundaries of multiple intellectual traditions and academic fields. The book analyses both historical trajectories and modern schools of thought while simultaneously exploring ethical applications to environmental and economic discourses as a tool of critique. In this context, the authors conceptualize and treat these discourses as polyvalent and enmeshed with various political, ethical, and cosmological perspectives and vistas.